Effects of cancer treatment during pregnancy on fetal and child development. (December 2017) - Vandenbroucke, Tineke; Verheecke, Magali; Fumagalli, Monica; Lok, Christianne; Amant, Frédéric
Summary: It has become clear that, for specific cancers and under well defined circumstances, oncological treatment in pregnancy is possible. In this Review, we summarise the evidence on fetal, neonatal, short-term, and long-term effects of prenatal exposure to cancer treatment on the child. So far, outcomes of children are generally reassuring, but long-term follow-up is insufficient. The most important risks of chemotherapy during pregnancy are preterm birth and babies being small for gestational age. Chemotherapy in the first trimester is contraindicated because of an increased risk of congenital malformations. Studies on outcomes of children exposed to radiotherapy, targeted therapy, or hormonal therapy in pregnancy are scarce. Careful registration of women undergoing cancer treatment in pregnancy and long-term follow-up of their children are important. Comprehensive documentation of the mental and physical status of children exposed to cancer treatment in utero will allow physicians and parents to best decide whether to treat cancer during pregnancy.